Fred & me - Bibby, Victor (Fremantle, Western Australia : Vivid Publishing, 2021)
A moving account of a child's removal from family and his institutionalised growing up in Australia, interwoven with a fascinating vignette of his father's life - from enlistment in WWI to his time at Gallipoli and later extraordinary life in England and subsequent return to Australia.
Keywords: Bibby, Victor; Bibby, Fred, -- 1898-1971.; Immigrant children -- Australia; Soldiers -- Australia -- Biography; Australians -- Great Britain -- Biography; Australian